Co-creating inclusive spaces and places: Towards an intergenerational and age-friendly living ecosystem - Fang, Mei Lan; Sixsmith, Judith; Hamilton-Pryde, Alison; Rogowsky, Rayna; Scrutton, Pat; Pengelly, Ro; Woolrych, Ryan; Creaney, Rachel (Frontiers in Public Health, 2023)
Introduction: Evolving ageing societies, ongoing digitalisation and circumstances of COVID-19 are changing living conditions for growing older. There is an increased urgency to view public health with a focus on integrating people of all ages into the matrix of opportunities afforded in their communities. This study initiates the conceptualisation of an intergenerational, age-friendly living ecosystem (AFLE) to enhance public health planning. Methodology: A participatory study was conducted using a multi-methods approach. Six virtual co-creation sessions (n=35-50 participants), alongside a mainly open-ended INTERGEN survey designed specifically for this study (n=130) were conducted to conceptualise multilevel ideas for building intergenerational age-friendly places using Bronfenbrenner’s ecological systems model. At the height of COVID-19, virtual applications (Zoom, Moodboard) and case studies, creative methods (drawing, photography, storytelling and spotlight sessions) were applied to engage academic and non-academic participants between ages 5 – 80+ years, across eight countries. Sessions were video-recorded with visual themes captured by a graphic facilitator. The survey covered issues of multigenerational interactions; intergenerational and age-friendly place features; place safety; and necessary stakeholders required for creating intergenerational and age-friendly places. Data were reflexively analysed using a team approach to thematic analysis. Results: Findings present both the thematic analysis of Virtual Co-creation Camps (VCCs) and the INTERGEN survey results. These findings are addressed in three overarching categories that highlight the necessary characteristics of AFLEs as suggested by the VCC participants and survey respondents: (i) Sensory factors: feeling and emotion as starting points for physical design; (ii) Physical and digital factors in designing AFLE spaces and places; and (iii) Socio-cultural factors: tackling ageism and exclusion as part of the solution. Discussion: The analysis resulted in a pathway towards enhanced understandings on how multi-generations can better interact with fluctuating organisational domains (industry, voluntary, academic and public sectors) in urban and rural settings to facilitate intergenerational connectivity. Through processes of co-creation, an AFLE proof of concept and roadmap for public health planning was developed to support and provide opportunities for people as they age to reap the socioeconomic benefits of their local and virtual communities and help them become well integrated, valued and contributory members of society.